2022
DOI: 10.2217/cer-2021-0178
|View full text |Cite
|
Sign up to set email alerts
|

Indirect comparison of apomorphine sublingual film and levodopa inhalation powder for Parkinson's disease ‘OFF’ episodes

Abstract: Aim: To compare efficacy of apomorphine sublingual film (APL) and levodopa inhalation powder (CVT-301) for ‘on-demand’ treatment of Parkinson's disease ‘OFF’ episodes. Patients & methods: Patient-level data from an APL pivotal study were re-weighted to match average baseline characteristics from a CVT-301 study (SPAN-PD). Placebo-adjusted treatments were compared at week 12. Results: Improvements in predose Unified Parkinson's Disease Rating Scale Part III scores were significantly larger for APL versus CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Recently, an indirect analysis of data from separate studies showed that sublingual apomorphine was superior to the recent introduced inhaled levodopa, improving UPDRS III scores at 30 and 60 minutes. 12 Unlike SC apomorphine which is available worldwide, sublingual apomorphine is only available in the United States and Canada, where it is licensed for sale in 10, 15, 20, 25, or 30 mg film strips. The starting dose recommended is 10 mg, followed by 5 mg increases after 72 hours, and the maximum single dose is 30 mg.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, an indirect analysis of data from separate studies showed that sublingual apomorphine was superior to the recent introduced inhaled levodopa, improving UPDRS III scores at 30 and 60 minutes. 12 Unlike SC apomorphine which is available worldwide, sublingual apomorphine is only available in the United States and Canada, where it is licensed for sale in 10, 15, 20, 25, or 30 mg film strips. The starting dose recommended is 10 mg, followed by 5 mg increases after 72 hours, and the maximum single dose is 30 mg.…”
Section: Discussionmentioning
confidence: 99%
“…Renewed interest in use of sublingual and intranasal apomorphine as an alternative to the SC route, is further supported by promising results from recent high‐quality trials, 54–56,66,67 especially for individuals with needle phobia. Recently, an indirect analysis of data from separate studies showed that sublingual apomorphine was superior to the recent introduced inhaled levodopa, improving UPDRS III scores at 30 and 60 minutes 12 . Unlike SC apomorphine which is available worldwide, sublingual apomorphine is only available in the United States and Canada, where it is licensed for sale in 10, 15, 20, 25, or 30 mg film strips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a comparison of the pivotal trials for inhaled LD and sublingual apomorphine Thach et al [ 42 ] compared placebo-adjusted treatments at week 12 from the SPAN-PD trial [ 43 ] and the CTH-300 trials [ 41 ]. There was no significant difference in the UPDRS part III score at the 15–20 minutes or the 30 minutes time points.…”
Section: Sublingual Apomorphinementioning
confidence: 99%